Tradisi Ziarah Makam Syekh Yusuf Pada Masyarakat Kontemporer Gowa Perspektif Hukum Islam - Haeni Mukti; Abdul Rauf Muhammad Amin; Nur Taufiq; Hamzah Hasan; Andi Muhammad Akmal (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
Syekh Yusuf al-Makassari, also known as Syekh Yusuf Abu MahasinHadiyatullah Ta al-Khalawati al-Makassari or simply Tuanta Salamaka ri Gowa (meaning "Our Great Teacher from Gowa"), was a prominent Islamic scholar,Sufi, and national hero of Indonesia. His tomb, located in Gowa, South Sulawesi,attracts people from both within and outside the region, who visit for variouspurposes, including fulfilling vows, making offerings, or simply praying for blessings and safety in this world and the hereafter. This research is an empirical legal study with a descriptive qualitative method. The research uses theological and anthropological approaches. The research findings show that, from the perspective of Islamic law, visiting graves is allowed as long as it meets the conditions and requirements according to the teachings of the Prophet Muhammad and does not deviate from these teachings. However, in the view of scholars, the tradition of visiting the Tomb of Syekh Yusuf, which is frequently practiced by the community, such as making vows, holding ceremonies, and asking for blessings, has varying opinions among scholars. Some permit it, while others prohibit it. It is advisable that when making a vow or asking for something, the community should fulfill it by holding a thanksgiving event or fasting as a form of gratitude to Allah SWT for the fulfillment of their vow.